Moderasi Beragama di Kalangan Minoritas Muslim di Indonesia - Ali Amran; Zaim Rais (Hikmah, 2025)
This study examines the practice of religious moderation among Muslim minority communities in Indonesia, particularly in regions where non-Muslims constitute the majority, such as Bali, East Nusa Tenggara, Papua, and North Sulawesi. Using a descriptive qualitative approach, the research explores the dynamics of religious life among Muslim minorities in practicing their faith, maintaining Islamic identity, and interacting socially with majority communities of different beliefs. Data were collected through in-depth interviews, participant observation, and document analysis from various local sources. The findings reveal that Muslim minorities often face several challenges, including social discrimination, restrictions on the construction of places of worship, and intolerant attitudes from segments of the community. In this context, the implementation of religious moderation principles—which include tolerance, non-violence, cultural accommodation, and national unity commitment—is seen as an effective approach to strengthening social cohesion and fostering harmonious coexistence. This study recommends the need for more inclusive, systematic, and context-sensitive public policies to support the sustainable practice of religious moderation. Such efforts are crucial to creating a safe, just, and equitable social space for all religious groups, especially for those in minority positions.